Análisis de evidencia de las investigaciones sobre conciencia y lenguaje 2000-2010 : una revisión sistemática (2012)
ABSTRACT: Owing to the relevance of theorization about language and consciousness, this study took up 86 research articles about these processes; published between the years 2000 and 2010. For the articles’ analysis of evidence, the Scottish Intercollegiate Guidelines Network (SIGN) was used. This made possible to identify the levels of evidence and categories of recommendations of the articles. In this study it was found that most of the researches reach a correlation-descriptive level. There were few studies that reach an explicative level. For the language studies, a transversal method is consistently used; meanwhile experimental designs are more recurrent in consciousness research. Articles about consciousness have higher levels of evidence and categories of recommendations compared to language studies. This fact unveils how the interest in the study of this process.